2011
DOI: 10.1145/2003616.2003635
|View full text |Cite
|
Sign up to set email alerts
|

Affecting attitudes in first-year computer science using syntaxfree robotics programming

Abstract: Persistence of first-year students in computer science is a problem. Although there are many factors that determine whether a student can be successful in computer science, research has shown that some attrition is due to personal perception of their ability in computer science. We created a learning experience specifically designed to improve students' self-assessment of their abilities. "Providing robotic experiences through objectbased programming" (PREOP) is a GUI programming environment based on Alice tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Robots have been used in both community outreach programs and academic institutions at all educational levels (M. Anderson et al, 2011), even in special needs education (Virnes et al, 2008). Robots, as physically manifested computing devices, inherently show students how the programs that they write can impact the real world.…”
Section: Robotics In Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Robots have been used in both community outreach programs and academic institutions at all educational levels (M. Anderson et al, 2011), even in special needs education (Virnes et al, 2008). Robots, as physically manifested computing devices, inherently show students how the programs that they write can impact the real world.…”
Section: Robotics In Educationmentioning
confidence: 99%
“…For example, the Scribbler robot (Summet et al, 2009), the iRobot Create (Anderson et al, 2011), the Topobo robot (Virnes et al, 2008), or the Thymio (Riedo et al, 2013). One of the most widely used educational robots is the LEGO ® MINDSTORMS ® kit.…”
Section: Robots and Robotics Competitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotics has an inherent appeal on both emotional and intellectual level that makes it attractive to a broad range of learners across multiple dimensions, such as age, gender, academic interest, or the chosen program of study. Robotics has become an increasingly popular topic to promote computing and use it as an engaging and motivational tool in introductory courses offered in middle and high schools, summer camps, as well as in CS 0 and CS I college-level courses [1,12]. This is very closely related to the increased availability of relatively cheap robotic platforms and kits, as well as inherent attractiveness of robotics and related technologies to the younger generation.…”
Section: Introductionmentioning
confidence: 99%
“…Always exploring different ways 24,25 to minimise the early drop-out rate, the first author of this paper devised a LEGO Physics Lab. (3) Prior research 26 has been undertaken where a specific learning experience using robots was offered prior to the core components of the course. This study was designed to improve student's self-assessment of their abilities in a first-year computer science course and it was found that students that rate their programming skill as average in comparison to their peers were most positively impacted.…”
mentioning
confidence: 99%